2002
DOI: 10.1186/cc1843
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: IntroductionThe term 'sepsis' is used to define the systemic inflammatory response to an infectious agent (i.e. bacterial, viral, fungal or parasitic). Despite the use of new treatment modalities, improvements in technology and increased experience, mortality rates in sepsis remain high [1,2]. Critical care physicians have at their disposal a variety of data to serve as a guide in discriminating infectious from noninfectious conditions in newly admitted patients. In a number of newly admitted patients the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
67
2
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(82 citation statements)
references
References 19 publications
(37 reference statements)
6
67
2
3
Order By: Relevance
“…Through various studies, procalcitonin was one of the markers which have been suggested for more rapid diagnosis of sepsis (Canan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Through various studies, procalcitonin was one of the markers which have been suggested for more rapid diagnosis of sepsis (Canan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Of these studies, Canan et al (2003) have stated that the procalcitonin sensitivity and specificity for differentiating SIRS from sepsis, is 85 and 91% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have evaluated the diagnostic utility of various biomarkers, including ferritin, haptoglobin, interleukin 6, C-reactive protein (CRP), and procalcitonin (PCT), for suspected sepsis in the ICU patient population (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). PCT has been the most-well-studied biomarker and has demonstrated the most promising results to date in the diagnosis of bacterial infection in a number of settings (16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%